Elaboramos reglas para mejorar el trabajo cooperativo en el aula - Garcia Rodriguez, Luis David (2020)
The session "Developing rules to improve cooperative work in the classroom", will be executed as part of the Personal Citizenship and Civic subject for students of the first grade of Secondary Education of the "Franklin Roosevelt School". The purpose of the session is to improve cooperative work in the classroom through rules which will be created by them. These rules will be created from knowledge they get in the development of the session. To achieve this, skills and performances, indicated in the learning session, as well as the elaboration of the final product, will be developed. Information and thematic field development were founded on the theoretical contributions of the constructivist pedagogical trend.